1988
DOI: 10.1126/science.2831625
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cell-Specific Expression of Rat Growth Hormone and Prolactin Genes by a Common Transcription Factor

Abstract: In the anterior pituitary gland, there are five phenotypically distinct cell types, including cells that produce either prolactin (lactotrophs) or growth hormone (somatotrophs). Multiple, related cis-active elements that exhibit synergistic interactions appear to be the critical determinants of the transcriptional activation of the rat prolactin and growth hormone genes. A common positive tissue-specific transcription factor, referred to as Pit-1, appears to bind to all the cell-specific elements in each gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
303
0
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(310 citation statements)
references
References 33 publications
5
303
0
2
Order By: Relevance
“…It is mainly expressed in the pituitary and its expression is necessary for the normal differentiation, development and survival of three adenohypophysis cell types, thyrotrophs, somatotrophs and lactotrophs (Li et al, 1990;Simmons et al, 1990). It is also important for the proper expression of growth hormone (GH ), prolactin (PRL) (Lefevre et al, 1987;Nelson et al, 1988), thyroid-stimulating hormone (TSH ) (Li et al, 1990) and POU1F1 gene itself (Chen et al, 1990;McCormick et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly expressed in the pituitary and its expression is necessary for the normal differentiation, development and survival of three adenohypophysis cell types, thyrotrophs, somatotrophs and lactotrophs (Li et al, 1990;Simmons et al, 1990). It is also important for the proper expression of growth hormone (GH ), prolactin (PRL) (Lefevre et al, 1987;Nelson et al, 1988), thyroid-stimulating hormone (TSH ) (Li et al, 1990) and POU1F1 gene itself (Chen et al, 1990;McCormick et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several homeodomain-containing proteins other than Gtx, including Pdx1 in the pancreas (Ohlsson et al, 1993;Ahlgren et al, 1996), TTF-1 in lung and thyroid (Lazzaro et al, 1991;Bruno et al, 1995), and Pit-1 in the pituitary (Nelson et al, 1988;Mangalam et al, 1989;Simmons et al, 1990), have been shown both to be expressed in terminally differentiated cells and to bind to the promoters of tissue specific genes, implicating them in their regulation. Both Pit-1 and Pdx1, however, are also expressed early in development of the pituitary (Li et al, 1990) and pancreas (Jonsson et al, 1994;Ahlgren et al, 1996), respectively, and inactivation of either their expression or their f unction has demonstrated that they also are necessary for normal organogenesis.…”
Section: Homeodomain Proteins Gtx and Developmentmentioning
confidence: 99%
“…7). In order to determine whether BrdU itself affected PRL producing cell induction, we performed the following three experiments: cells were incubated with [1] insulin and EGF for 24 h, [2] BrdU for 24 h and [3] normal medium for 24 h and then subjected to double labeling immunocytochemical staining for BrdU and PRL, as described above. These preliminary experiments showed that BrdU itself did not affect PRL-producing cell differentiation (data not shown).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…In order to analyze the relationship between cell proliferation and differentiation, MtT/S cells were cultivated under three different growth conditions: they were cultivated [1] in growth medium and harvested 0,12 and 24 h after adding insulin and EGF (control group); [2] in 1/4 serum medium for 7 days, the medium was replaced with growth medium, and differentiation into PRL-producing cells was induced by incubation with insulin and EGF for 0,12 and 24 h (growth group) and, [3] in 1/4 serum medium for 7 days and then stimulated with insulin and EGF for 0,12 and 24 h (starvation group). After cultivation, the cells were dispersed with 0.025% trypsin, washed twice with calciumfree phosphate-buffered saline (PBS) and fixed with 70% ethanol at 4 °C.…”
Section: Flow-cytometry and Cell Sortingmentioning
confidence: 99%